A New Paradigm on Human Resources Management in State Islamic University - As'ad As'ad; Firmansyah Firmansyah; Arfan Arfan (STAI Hubbulwathan Duri, 2022)
This paper analyzes literature and field studies that focuses on the science-religion integration paradigm in state Islamic universities or Universitas Islam Negeri (UIN), which covers integration and interconnection discourse at UIN Sunan Kalijaga Yogyakarta, UIN Maulana Malik Ibrahim Malang, and UIN Syarif Hidayatullah Jakarta and relating this topic to human resources study. There are three objectives of this study: to delve into the science-religion integration paradigm, to know the epistemology discussion of science-religion integration in three Islamic state universities, and to study the importance of integration-interconnection paradigm in Muslim societies human resources. The study found that the epistemology of the integration-interconnection of science-religion is a dynamic discourse that will simultaneously continue to develop; secondly, the three Islamic universities have laid the foundations of an important paradigm of the relationship between science and religion, in terms of discourse and the curriculum of the three universities which will affect to the young human resource provision landscape. Third, the integration paradigm of Islamic higher education has offered a new paradigm of human resources management in Muslim societies. The integration of science and religion paradigm will provide non-dichotomous human resources through Islamic universities in the future.